Comparative Error Analysis In Writing Recount Text Made By The First And The Third Semester Students Of English Department UMS 2014/2015 Academic Year - Perdana, Hestuningtyas Maharani; , Prof. Dr. Endang Fauziati, M. Hum; , Nur Hidayat, S. Pd, M. Pd (2015)
The objectives of the study are to describe the types of error made by the first and the third semester students of English Department UMS 2014/ 2015 academic year and to find the similarities and the differences of the types of error which are made by the first and the third semester students of English Department UMS 2014/ 2015 academic year. This study is qualitative research. The data are taken from all interlanguage errors which are made by the student's writing recount text. The technique for analyzing data is by exploring, reducing, categorizing, and checking the data validity. The results of this study are: (1) the types of error which are found on the first and the third semester students are morphological error and syntactical error. Syntactical error is the most types of error, which has appeared, (2) the similar types of error that are made by the first and the third semester students is morphological and syntactical error, (3) the differentt types of error happened in the syntactical error only. There were some types of error that made by the first semester students but the third semester students did not, namely in omission of indefinite article (a/ an), omission of introductory THERE as subject, verb II is used after 'modal' form, misplace of conjunction, omission of phrasal verb, omission of preposition in the sentences, and wrong arrangement of phrase.